"A normal amount of masculine hardness": representations of male nurses in 1960s West Germany - Schwamm, Christoph (Canadian bulletin of medical history, 2019)
The nursing studies narrative of the role of masculinity can be summarized as follows: hegemonic masculinity prevents men from doing care work. An analysis of public relations efforts to recruit male nurses in West Germany during the 1960s does not provide evidence for such a link. Representing nursing as compatible with hegemonic masculinity was also able to legitimize the existence of male nurses, while the idea of promoting gender equality in nursing was advocated by exactly those institutions that enabled the eventual gender inequality within the profession. Finally, the thesis of hegemonic masculinity as some kind of anti-caregiving agent comes into question because of the success of the civilian service in West Germany, despite the gender shaming used to deter men from enlisting in it.
Gesehen am 08.09.2021